A novel mechano‐enzymatic cleavage mechanism underlies transthyretin amyloidogenesis - Julien Marcoux; P Patrizia Mangione; Riccardo Porcari; Matteo T Degiacomi; Guglielmo Verona; Graham W Taylor; Sofia Giorgetti; Sara Raimondi; Sarah Sanglier‐Cianférani; Justin LP Benesch; Ciro Cecconi; Mohsin M Naqvi; et al. (EMBO Molecular Medicine)
Abstract The mechanisms underlying transthyretin‐related amyloidosis in vivo remain unclear. The abundance of the 49–127 transthyretin fragment in ex vivo deposits suggests that a proteolytic cleavage has a crucial role in destabilizing the tetramer and releasing the highly amyloidogenic 49–127 truncated protomer. Here, we investigate the mechanism of cleavage and release of the 49–127 fragment from the prototypic S52P variant, and we show that the proteolysis/fibrillogenesis pathway is common to several amyloidogenic variants of transthyretin and requires the action of biomechanical forces provided by the shear stress of physiological fluid flow. Crucially, the non‐amyloidogenic and protective T119M variant is neither cleaved nor generates fibrils under these conditions. We propose that a mechano‐enzymatic mechanism mediates transthyretin amyloid fibrillogenesis in vivo. This may be particularly important in the heart where shear stress is greatest; indeed, the 49–127 transthyretin fragment is particularly abundant in cardiac amyloid. Finally, we show that existing transthyretin stabilizers, including tafamidis, inhibit proteolysis‐mediated transthyretin fibrillogenesis with different efficiency in different variants; however, inhibition is complete only when both binding sites are occupied.